- 1 - Analysis of the role of social support - cognitive psychology and emotional process approach - Mohammad Heydari; Zhou Xiaohu; Mahdiye Saeidi; Kin Keung Lai; Yufan Shang; Zheng Yuxi (PAGEPress Publications, 2020)
The eyes are extremely important for communication. The muscles around the eyes express emotional states, and the size of the pupil signals whether a person is aroused and alert or bored and fatigued. Pupil size is an overlooked social signal, yet is readily picked up by observers. Observers mirror their pupil sizes in response, which can influence social impressions. Pupil diameter is enhanced in a variety of emotional contexts, including viewing pictures, listening to sounds, and during the threat of shock. This study shows that people associate positive faces with large pupil sizes and negative faces with small pupil sizes. Although workplace social support has been described as a profoundly emotional activity, little is known about the emotional demands faced by employees or how these impacts on their well-being. This study examined relationships between 'emotional labor,' burnout (emotional exhaustion, depersonalization, and personal accomplishment), and job satisfaction in a sample of an employee who works in the banking sector or manufacturing sector. Also examined was whether workplace social support moderated any relationships found between emotional labor and strain. The relationship between job experience and emotional labor was also investigated.